Success of felling and reforestation in weakened pine forests in the fresh relatively infertile pine site type in Klavdiievo Forest Research Station - Савущик, М. П. (Forestry and Forest Melioration, 2024)
Introduction Research on the success of natural pine regeneration in various forest site conditions in Kyiv Polissia has been carried out for many decades. The long-term studies of the natural regeneration of pine stands have not revealed a universal approach even within the same forest site type region. The influence of many variable factors on natural regeneration explains this fact. Therefore, the regularities found in one region's forests cannot be transferred to another, which requires further systematic research. The study aimed to assess the stand state dynamics and the success of different methods of pine stand regeneration in the case of gradual and continuous felling in the fresh oak-pine forest site type in Kyiv Polissya. Materials and Methods The object of research was the experimental and production plot established in 2008. Continuous sanitary felling was planned in the subcompartment. A part of the plot (3 hectares in area) was used for research. The two-section experiment was established in a weakened uneven-aged pine stand, which grows in a fresh oak-pine forest site condition. In the first section of 2 ha of the experiment, continuous felling was carried out and seed trees were left, while in the second section of 1 ha, the first stage of evenly-gradual felling was applied. Field data were collected and processed based on generally accepted forestry and mensuration. Results According to the survey of the experimental site in the autumn of 2023, the pine trees in the section of continuous felling intensively grew. An average height was 7.1 m and an average diameter of 7.2 cm corresponding to 1a site class. The stand was fully stocked (the average relative stocking density was 0.8). It was uneven and needed to be cleaned. The forest stand was partially damaged because of hostilities. In the gradual felling section as of 2008, 486 trees were growing. The first stage of gradual felling was high intensity (70% of the stock). After that, 129 trees were left in the section, of which 124 were pines and 5 oaks. A drastic change in the growth conditions of the abandoned part of the stand caused the death of trees. The most significant decline occurred during the first five years after the felling: 46% of the initial number of left trees died. After the felling was completed, measures were taken to promote natural regeneration. In the spring of 2009, the soil was partially plowed up and in 2010 pine seeds were additionally sowed. The natural regeneration of the section was recorded in 2011, 2013, 2015 and 2023. As of autumn 2023, the success of natural regeneration according to the scale developed in URIFFM was evaluated as “insufficient”. The amount of pine undergrowth was less than the standard specified in the Rules of Final Felling for the final stage of evenly gradual felling. Conclusions The results of long-term research at the experimental and production site show that in a fresh oak-pine forest site condition in State Enterprise “Klavdiievo Forest Research Station” evenly-gradual felling in weakened pine stands does not ensure successful forest regeneration according to the standards of the current Rules of Final Felling in the Forests of Ukraine, even together with soil mineralization and additional sowing of seeds as measures to promote natural regeneration. However, forest sowing in a clear-cut area has been successful. Therefore, it can be assumed that evenly-gradual felling could be applied followed by combined regeneration. However, when planning additional research, it should be considered that in weakened pine stands, with a high intensity of the first stage of evenly gradual felling, the intensive tree decline will occur in the left part of the stand during the first years. 4 Figs., 11 Refs.